Data base: Pinus ponderosa seedlings - Nursery genetic trial [Conjunto de datos] - Aparicio, Alejandro Gabriel (2024)
Supplementary dataset to the article "Mitochondrial DNA lineages and genetic variation of early growth traits in the Argentinean breeding population of Pinus ponderosa Douglas ex C. Lawson", New Forests : 1-21 (Published: 05 March 2024)